Exploring the Impact of Civic Education on Civic Participation Among Elementary School Students: Mengeksplorasi Dampak Pendidikan Kewarganegaraan terhadap Partisipasi Kewarganegaraan di Kalangan Siswa Sekolah Dasar - Rahayu, Kanti; Yunitasari, Dinar; Utaminingsih, Esty Setyo; Purwaningsih, Indah; Sari, Febria Indah (Universitas Muhammadiyah Sidoarjo, 2024)
Civic education is an urgency that must be considered in elementary schools, considering that current technological developments in the world have entered the era of digitalization 5.0. The purpose of writing this article is to examine further the importance of civic education for students in elementary schools. The writing method in this article uses literature study, a series of activities relating to methods of collecting library data, reading and taking notes, and processing various references that are related and relevant to the problem being studied. The existence of civic education in elementary schools equips students to become good citizens with good character, tolerance, and critical thinking. However, it is hoped that it can create moral citizens with superior character. Highlights: Civic education in elementary schools fosters good citizenship by instilling values of tolerance and critical thinking. Digitalization 5.0 underscores the urgency of integrating civic education to navigate modern societal challenges. The aim is to cultivate moral citizens with superior character through structured curriculum and interactive learning methods. Keywords: civic education, elementary school, character